CAF-mediated regulation of prostate cancer stem cell stemness via the Wnt/β-catenin and SDF-1/CXCR4 pathways in castration-resistant prostate cancer - Chen, Haoran; Li, Zhen; Yue, Yuan; Zhu, Xudong; Wang, Jiazheng; Chen, Yafei; Wang, Yilin; Luo, Zhanyang; Liu, Hao (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe role of cancer-associated fibroblasts (CAFs) in the progression, therapeutic resistance, and metastasis of castration-resistant prostate cancer (CRPC) remains incompletely understood. This study aimed to investigate how CAFs regulate the stemness of prostate cancer stem cells (PCSCs), with a focus on the Wnt/β-catenin and SDF-1/CXCR4 signaling pathways.MethodsWe assessed the expression of CAF and PCSC markers in xenograft tumor tissues from hormone-sensitive prostate cancer and CRPC mouse models using immunohistochemistry and immunofluorescence. The impact of CAFs on stemness markers, SDF-1, CXCR4, and Wnt pathway activation was evaluated both in vitro and in vivo.ResultsThe expression levels of CAF and PCSC markers were significantly elevated in CRPC tissues compared to hormone-sensitive tumors. Bioinformatics analysis indicated high expression of CXCR4 and CTNNB1 (β-catenin) in CRPC, with positive correlations to disease progression. CAFs enhanced PCSC stemness, while inhibition of Wnt3a or SDF-1 led to reduced stemness and pathway activity. In vivo, CAFs promoted CRPC tumor growth and significantly increased the expression of Wnt3a, β-catenin, TCF4, LEF1, SDF-1, and CXCR4, along with an elevated p-GSK-3β/GSK-3β ratio. Conversely, β-catenin and CXCR4 inhibitors suppressed tumor growth and downregulated Wnt signaling components.Discussionβ-Catenin and CXCR4 showed strong co-localization in xenograft tumors. These findings suggest that CAFs promote PCSC stemness and CRPC progression by activating the Wnt/β-catenin and SDF-1/CXCR4 pathways via Wnt3a and SDF-1 expression. These insights provide potential targets for managing CRPC.